DIABETES CONTROL AMONG ELDERLY DIABETIC PATIENTS IN KUANTAN, MALAYSIA - Aris, Mohd Aznan Md; Zulkifli, Syazana Aqilah; Shalihin, Mohd Shaiful Ehsan; Aidid, Edre Mohammad (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND The transformation of the aging population in Malaysia carries a significant healthcare burden in chronic diseases like Type 2 Diabetes Mellitus (T2D). METHODOLOGY This study aims to measure the patients’ diabetes control and to identify its related factors among elderly diabetic patients in Kuantan. This cross-sectional study was conducted in six selected government health clinics in Kuantan (chosen from stratified random sampling) where 300 elderly patients with T2D were recruited via proportionate random sampling. The related factors studied were sociodemographic profile, health and treatment characteristics and quality of life using the RVDQOL13 questionnaire. The data were analysed using SPSS version 26. RESULTS The mean age of the patients was 68.1 years old (SD=6.009). Most patients were female (57.3%), Malay (70.3%), married (66%), living independently (Modified Barthel Index = 99%) and from B40 (96.3%). The prevalence of good diabetes control was 59.3% (cut-off point = HbA1c ≤7.5%). The significant predictors for good diabetes control identified were non-Malay (aOR = 3.92, 95%CI 1.907-8.060, p <0.001), treatment with insulin injection (aOR = 0.193, 95%CI 0.094- 0.395, p <0.001), abnormal capillary blood glucose (CBG) (aOR = 0.655, 95%CI 0.489-0.878, p <0.001), having higher LDL-C (aOR = 0.655, 95%CI 0.489-0.878, p = 0.005), and poor satisfactory impact from RV-DQOL13 (aOR = 0.919, 95%CI 0.884-0.954, p <0.001). CONCLUSION Elderly diabetic patients in Kuantan have good diabetes control. However, follow-up for this group needs to be emphasized among Malay patients, those on insulin treatment, poor CBG during TCA, high LDL-C and those who are unsatisfied with diabetes care to maintain good diabetes control prevalence.